Microwave-assisted Synthesis of Pyrroles, Pyridines, Chromenes, Coumarins, and Betti Bases via Alcohol Dehydrogenation with Chroman-4-one Amino Ligands - Khan, Danish; Kumari, Beauty; Alzahrani, Abdullah Yahya Abdullah; Dua, Neha; Shaily; Maurya, Nirma (Current Organic Chemistry, 2024)
This study outlines the development of a novel approach utilizing microwave assistance for the alcohol dehydrogenative reaction. The process is catalyzed by manganese (II) and cobalt (II) in conjunction with chroman-4-one amino ligands. This research introduces a unique catalytic system capable of synthesizing various heterocyclic compounds, including pyrroles, pyridines, Betti bases, chromenes, and coumarins via alcohol dehydrogenation. The synthesis involved the preparation and characterization of a series of chroman-4-one amino ligands (C1-C6) using standard analytical techniques. These ligands, in combination with MnCl2‧4H2O and CoCl2, demonstrated remarkable catalytic activity, effectively driving alcohol dehydrogenation. The catalytic cycle was initiated by the in-situ formation of metal complexes with the ligands during the reaction. Characterization using ESI-MS confirmed the presence of metal complexes (Int-1) and other intermediates (Int-II and Int-III) throughout the catalytic cycle. Additionally, the controlled experiment corroborated the efficacy of the catalytic system, evidenced by the evolution of H2 gas.
Keywords: pyrrole